Role of Light Physical Activity Towards Stress in the Elderly in Nursing Homes - Nesia, Waynhena Sarawa; Atmodjo, Wahyuni Lukita; Moningkey, Shirley Ivonne (Medicinus, 2023)
Introduction: It was reported that one in five adults and four out of five adolescents around the world did not do enough physical activity, especially the elderly tend not to do physical activity that is classified as active. Less physical activity can inhibit the release of ACTH and decrease cortisol secretion so that it can cause stress. Although it has been reported about the relationship between physical activity and stress levels at the age of 23-54 years, there has not been much research on the relationship in the elderly. Many elderly people aged over 60 years, especially those living in nursing homes experience stress due to lack of physical activity. Thus, further research is needed regarding the relationship between light physical activity and stress levels in the elderly at the Nursing Home.Methods: It was an unpaired categorical comparative analytic study. Elderly respondents at the Nursing Home aged 60-74 years will fill out the PASE questionnaire to assess physical activity and the PSS-10 to assess stress levels. The data obtained will be processed using Microsoft Excel and analyzed with the Pearson Chi-Square test using the SPSS-25 program.Result: Of the 40 respondents, 30 did light physical activity and 10 did heavy physical activity. It was also found that 14 experienced mild stress and 26 experienced severe stress. The results from Pearson ChiSquare show p-value <0.001 and OR = 16.000.Conclusions: The results of this study states that there is a significant relationship between light physical activity and stress levels in the elderly aged 60-74 years who live in nursing homes.